Strategi Komunikasi CEO Citibank, N.A. dalam Mengelola Komunikasi Internal Selama Krisis Global 2008. - Lukas Maserona Sarungu (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
Good communication between the top management of a company and its employees is important, especially in times of crisis. This article attempts to study the communication strategy adopted by the CEO (Chief Executive Officer) of Citibank, N.A., Vikram Pandit, in managing the company's internal communications during the 2008-2011 global financial crisis. This study is important to be used as a lesson for academic theorists and corporate practitioners, because, in addition to adding insight and literature on related topics, it can also be used as a reference for managers in practicing strategic communication in companies. This research uses the narrative analysis method to learn strategy employed by the CEO of Citibank, N.A. in communicating with employees around the world. The result of this study is that integrity, transparency, and prioritizing employees are important for companies to get through times of crisis.